Analisis Sistem Manajemen Sekuriti : K3 dan Beban Kerja di PT.Bridgestone - Daffa Khuzaimy Ghozali; Sheva Rafif Rabbani; Muhammad Fadli Absari; Muhammad Al Fikri Haikal; Jasson Arfian (Journal of Informatic and Information Security, 2024)
This research aims to analyze the effectiveness of the security management system, Occupational Safety and Health (K3), as well as workload at PT Bridgestone. Three aspects This is an important pillar in maintaining smooth operations, employee safety, and security of company assets. As a large manufacturing company, PT Bridgestone facing complex challenges in implementing strict security management, effective K3 policies, and balanced workload arrangements for employees. This research method includes qualitative and quantitative approaches with techniques data collection through observation, interviews and questionnaires to employees and management. Data analysis was carried out to evaluate the extent of the management system security and K3 have been implemented, as well as to identify factors that affect employee workload. The research results show that still there are several areas that require improvement, such as procedural adjustments security, increased compliance with K3 standards, and workload management which is more regular. Recommendations resulting from this research include strengthening the management system security with supporting technology, regular K3 training for all employees, as well as adjusting workload to suit individual capacity. System implementation More integrated management is expected to be able to create a work environment which is safer, more productive and conducive at PT Bridgestone.